Transmission and control of SARS-CoV-2 on ground public transport: A rapid review of the literature up to May 2021. (September 2022) - Gartland, Nicola; Fishwick, David; Coleman, Anna; Davies, Karen; Hartwig, Angelique; Johnson, Sheena; van Tongeren, Martie
Abstract: Background: During a pandemic, public transport is strategically important for keeping the country going and getting people where they need to be. The essential nature of public transport puts into focus the risk of transmission of SARS-CoV-2 in this sector; rapid and diverse work has been done to attempt to understand how transmission happens in this context and what factors influence risk. Objectives: This review aimed to provide a narrative overview of the literature assessing transmission, or potential for transmission, of SARS-CoV-2 on ground-based public transport, as well as studies assessing the effectiveness of control measures on public transport during the early part of the pandemic (up to May 2021). Methods: An electronic search was conducted using Web of Science, Ovid, the Cochrane Library, ProQuest, Pubmed, and the WHO global COVID database. Searches were run between December 2020 and May 2021. Results: The search strategy identified 734 papers, of which 28 papers met the inclusion criteria for the review; 10 papers assessed transmission of SARS-CoV-2, 11 assessed control measures, and seven assessed levels of contamination. Eleven papers were based on modelling approaches; 17 studies were original studies reporting empirical COVID-19 data. Conclusions: The literature is heterogeneous, and there are challenges for measurement of transmission in this setting. There is evidence for transmission in certain cases, and mixed evidence for the presence of viral RNA in transport settings; there is also evidence for some reduction of risk through mitigation. However, the routes of transmission and key factors contributing to transmission of SARS-CoV-2 on public transport were not clear during the early stage of the pandemic. Gaps in understanding are discussed and six key questions for future research have been posed. Further exploration of transmission factors and effectiveness of mitigation strategies is required in order to support decision making. Highlights: COVID-19 transmission can occur on public transport. Relative importance of COVID-19 transmission routes on public transport unknown. Masks, ventilation, and social distancing reduce risk on public transport. Current evidence and knowledge gaps need to be addressed to improve risk assessment. Current studies are underway in the UK to address some of these evidence gaps.